2018
DOI: 10.18203/2349-3933.ijam20175878
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between dexamethasone and dexmedetomidine in supraclavicular block

Abstract: INTRODUCTIONPeripheral nerve block has taken patient care in anaesthesia to a whole new level. Because of the advent of nerve stimulator and peripheral nerve block techniques, even patients in ASA grade 3 and 4 can be taken up for surgery safely. Moreover, with the use of adjuvants in brachial plexus block (BPB), one can extend patient care in the form of extended postoperative analgesia, ensure compliance of patient with physiotherapy and early mobilization of patient with stable haemodynamic variables. Dexme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
(8 reference statements)
2
10
0
3
Order By: Relevance
“…Both animal [144] and human volunteer [145] studies indicate that unlike dexamethasone, dexmedetomidine exerts its anti-nociceptive effects locally, through perineural mechanisms. Hence, it is not surprising that we found perineural dexmedetomidine to hasten the sensory and motor onset times compared with dexamethasone, as observed in previous studies [146].…”
Section: Discussionsupporting
confidence: 87%
“…Both animal [144] and human volunteer [145] studies indicate that unlike dexamethasone, dexmedetomidine exerts its anti-nociceptive effects locally, through perineural mechanisms. Hence, it is not surprising that we found perineural dexmedetomidine to hasten the sensory and motor onset times compared with dexamethasone, as observed in previous studies [146].…”
Section: Discussionsupporting
confidence: 87%
“…Time to request of first rescue analgesia was also prolonged in group Dexmed (930 ± 83.45 min) than in group Dexa (620 ± 125.54 min), which is clinically and statistically significant ( Table 2). Our results were similar to the results obtained by Verma NK et al and Kaur M et al 13,14 However Lee MJ et al observed that the sensory blockade was prolonged with dexmedetomidine or dexamethasone as adjuvants compared to plain ropivacaine, but there was no significant intergroup difference between dexmedetomidine and dexamethasone. Significant differences in onset time was not noticed among three groups, which is attributable to the higher dose of local anaesthetic.…”
Section: Discussionsupporting
confidence: 91%
“…11 Kaur et al compared the effects of 8 mg of dexamethasone with 50 µg of dexmedetomidine as an adjuvant with a mixture of 20 ml of 2% lignocaine with adrenaline and 18 ml of 0.5% bupivacaine in supraclavicular block. 16 They found that dexmedetomidine prolonged the block when compared with dexamethasone. Contrary to these studies, our study showed a significantly prolonged block with dexamethasone.…”
Section: Discussionmentioning
confidence: 99%